Distance, presence, access. Beyond walls and digital cages - Buffardi, Annalisa (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The paper shows the findings of some research in the field of distance learning among university students, secondary schools students and in the segment of adult education. It also provided data about smart working in the Covid-19. The aim of the present work is, particularly, to highlight some outcomes related to the perception of the distance experiences carried out during the pandemic emergency. Among the participants in the surveys, a significant evaluation plan refers to the management of daily life in the online network. The outcomes underscore opportunities, limits, and, therefore, the parallel demand for social organization of DaD and smart working.